Improving University Competitiveness Through Blue Ocean Strategy Based Co Creation Strategy - et al., Ratih Hurriyati (International Journal of Advanced Science and Technology, 2019)
Universitas Pendidikan Indonesia (Indonesia University of Education or later be called UPI) as PT PKBLU (Tertiary Education Institution with Financial Management of Public Service Body) needs to act and to position the institution effectively, efficiently and with accountability. To get effective and efficient work, UPI must develop a careful strategy. Therefore, UPI must think far ahead towards the alternative strategies, which are radically able to maximize the opportunities that exist and at the same time minimize the risk to achieve the best goals and objectives and to benefit UPI itself. Thus, this study examines innovative and creative strategies with the Co Creation Strategy approach that creates new market spaces without competitors and leaves competition irrelevant. The results of this study are innovative strategic models through a model that can be integrated and applied to the measurement of educational organizations' competitiveness through academic activities and encourage the quality of education as a whole and sustainably